Professional guide to pathophysiology - Laura wills; Willis, Laura M., 1969- (Philadelphia : Wolters Kluwer, 2020)
"Although pathology changes very little, our understanding of pathophysiology is constantly changing as it is enriched by new scientific research. Indeed, research has contributed greatly to our knowledge base regarding normal physiology as well as disease states. This fourth edition of Professional Guide to Pathophysiology reflects such recent advances in medical knowledge. The first chapter of the book lays a foundation for normal cellular physiology and pathologic deviations of disease. Following that, cancer, infection, and fluid and electrolytes each deserve a specific chapter because of their ubiquitous effects. The remainder of the book is organized by body system, with an initial discussion of normal anatomy and physiology as a background for pathology specific to that area. Subsequent disease entries cover causes, pathophysiology, signs and symptoms, complications, diagnosis, treatment, and special considerations. Professional Guide to Pathophysiology, Fourth Edition, readily provides the vital information needed, helping the clinician keep current and helping the student emerge more knowledgeable"--
Includes bibliographical references and index.
Keywords: Pathology; Physiological Phenomena; Pathologic Processes